2012
DOI: 10.1111/j.1558-5646.2012.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis and Experimental Evidence Indicate That the Earliest Trace Fossil of a Winged Insect Was a Surface-Skimming Neopteran

Abstract: A recent description and analysis of an imprint fossil from the Carboniferous concluded that it was made by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…A full body impression of a putative Carboniferous (Westphalian B/C) mayfly is subject to controversy (Benner et al, 2013;Knecht et al, 2011;Marden, 2013aMarden, , 2013b. Bojophlebia prokopi Kukalová-Peck, 1985 (Westphalian C) is likely outside of Palaeoptera, according to descriptions and phylogenetic analysis (Prokop et al, 2010;Sroka et al, 2015;Staniczek et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A full body impression of a putative Carboniferous (Westphalian B/C) mayfly is subject to controversy (Benner et al, 2013;Knecht et al, 2011;Marden, 2013aMarden, , 2013b. Bojophlebia prokopi Kukalová-Peck, 1985 (Westphalian C) is likely outside of Palaeoptera, according to descriptions and phylogenetic analysis (Prokop et al, 2010;Sroka et al, 2015;Staniczek et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The reply of Benner, Knecht, and Engel (hereafter BKE) to my critique (Marden ) of their paper (Knecht et al. ; hereafter KEB) describing the earliest trace fossil of a winged insect consists primarily of accusations of methodological failings on my part, but our differences have nothing to do with methods.…”
Section: Objection 1 Regarding Marks Alongside the Bodymentioning
confidence: 93%
“…The most recent and taxonomically appropriate developmental genetic study (Niwa et al ) concluded that mayfly wings show evidence for a mixture of appendage (i.e., possibly gill) and body wall origins. My critique (Marden ) included a video (EVO_1743_sm_video_S2.dv) showing the first evidence that the abdominal segmental gills present in certain Odonata (Polythoridae) are flappable. Another recent study found exquisitely preserved and apparently flappable segmental gills in a newly discovered sister taxon of mayflies, the Coxoplectoptera (Staniczek et al ).…”
Section: Objection 1 Regarding Marks Alongside the Bodymentioning
confidence: 99%
“…), a welcome and normal part of discovery, research, and discussion. Here we question the overall methodology by which Marden () drew conclusions, ultimately questioning their validity. Marden's () portrayal of the data gleaned from the trace fossil specimen from the Pennsylvanian (Westphalian) Wamsutta Formation of southeast Massachusetts (Knecht et al.…”
mentioning
confidence: 99%
“…Here we question the overall methodology by which Marden () drew conclusions, ultimately questioning their validity. Marden's () portrayal of the data gleaned from the trace fossil specimen from the Pennsylvanian (Westphalian) Wamsutta Formation of southeast Massachusetts (Knecht et al. ; University of Kansas, Entomological Collections SEMC‐F97) effectively results in misinformation regarding the fossil itself, and subsequently its interpretation.…”
mentioning
confidence: 99%